Peningkatan Kapasitas Kelompok Masyarakat Melalui Pelatihan Komunikasi Interpersonal di Kelurahan Cidurian Selatan - Aini, Rahmi; Yuliansyah, Teuku; Maulana, Shandy; Hilmy Putri, Himyar; Fitrananda, Charisma (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2022)
In domestic life, communication between spouses is very important in realizing family harmony. The city of Bandung is experiencing problems with interpersonal communication between married couples. The problems experienced have not found the best solution in an effort to maintain domestic relationships and even almost divorced. This condition occurs in couples who are over 5 years old in a domestic relationship. This lack of good interpersonal communication skills results in prolonged conflicts and the non-realization of a happy and harmonious home life. Based on the identification of problems with partners, the solution offered is to improve interpersonal communication between married couples in the community group of South Cidurian Village, Buahbatu District, Bandung City. . The method to be carried out is training. The results of the training showed that interpersonal communication skills between couples in South Cidurian Village became more effective and realized harmony in the household.